1991
DOI: 10.1002/jcp.1041480119
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for spatial and temporal regulation of transforming growth factor β1 expression during cutaneous wound healing

Abstract: The expression of transforming growth factor (TGF beta 1) protein in human and porcine skin has been analyzed by immunohistochemistry with two polyclonal antibodies (anti-CC and anti-LC) following cutaneous injury. The anti-LC antibody binds intracellular TGF beta 1 constitutively expressed in the nonproliferating, differentiated suprabasal keratinocytes in the epidermis of normal human skin, while the anti-CC antibody does not react with the form of TGF beta 1 present in normal skin as previously shown. TGF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(139 citation statements)
references
References 51 publications
5
130
1
3
Order By: Relevance
“…Although TGF-, I is able to reverse many effects of corticosteroid administration and age-related phenomena, it is not clear how this reversal is mediated. Modulation ofwound repair by TGF-, 1 is complex and involves multiple levels of control (see review by Sporn and Roberts [25 ] ), and depends on the presence of other growth factors or regulatory peptides (7,26,27), the target cell, and the cell's state of differentiation (for examples, see Janat and Liau [28] or Celada and Maki [29 ]). TGF-,B1 's action on neutrophils (30) and monocytes (31 ), as well as other cell types, is presumably mediated through membrane-bound receptors that when activated stimulate cytoplasmic and nuclear responses resulting in a cascade of cellular and extracellular events (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TGF-, I is able to reverse many effects of corticosteroid administration and age-related phenomena, it is not clear how this reversal is mediated. Modulation ofwound repair by TGF-, 1 is complex and involves multiple levels of control (see review by Sporn and Roberts [25 ] ), and depends on the presence of other growth factors or regulatory peptides (7,26,27), the target cell, and the cell's state of differentiation (for examples, see Janat and Liau [28] or Celada and Maki [29 ]). TGF-,B1 's action on neutrophils (30) and monocytes (31 ), as well as other cell types, is presumably mediated through membrane-bound receptors that when activated stimulate cytoplasmic and nuclear responses resulting in a cascade of cellular and extracellular events (32).…”
Section: Discussionmentioning
confidence: 99%
“…The local production of growth factors such as TGF-# 1 or PDGF has been associated with various stages of tissue repair (7,8). With the recent availability of large amounts of these factors through recombinant techniques, several investigators have shown that the local application ofgrowth factors accelerates tissue repair in animal models of wound healing (9-1 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several publications report on the presence of TGF-␤s in wound fluid of different species (27,35,204,281). Furthermore, expression of all three isoforms was detected in many different cell types during repair, with each isoform having a characteristic distribution in the wound tissue (91,141,157,238,270,271). In most studies, a rapid induction of TGF-␤1 and -␤2 was observed, whereas an increase in TGF-␤3 expression was seen at later stages of repair.…”
Section: A Expression Of Tgf-␤ At the Wound Sitementioning
confidence: 99%
“…TGFP1 has been immunologically demonstrated in the suprabasal cell layers of normal human (26) and mouse epidermis (27). In an elegant study, Kane et al (26) recently provided immunological evidence that skin expresses an inactive TGFO-precursor, which is proteolytically activated and released immediately upon injury.…”
Section: The Hierarchy Of the Epidermal Cytokine Networkmentioning
confidence: 99%